2022
DOI: 10.1523/jneurosci.1812-21.2022
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Dynamics of Neural Responses in Human Visual Cortex

Abstract: Neural responses to visual stimuli exhibit complex temporal dynamics, including sub-additive temporal summation, response reduction with repeated or sustained stimuli (adaptation), and slower dynamics at low contrast. These phenomena are often studied independently. Here, we demonstrate these phenomena within the same experiment and model the underlying neural computations with a single computational model. We extracted time-varying responses from electrocorticographic (ECoG) recordings from patients presented… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(79 citation statements)
references
References 66 publications
7
39
1
Order By: Relevance
“…Going further than previous studies, we were able to show how multiple features of the same stimulus are coded simultaneously and sustained for prolonged periods. This prolonged coding of each feature support prior research showing feature coding in multiple areas of the visual pathway beyond V1 (e.g., Desimone et al, 1985;Groen et al, 2022;Kamitani and Tong, 2005;Marquardt et al, 2018;Seymour et al, 2009). We found distinct representations for each feature, reflecting separable neural populations and/or different codes of multiplexing cells specialised for coding each feature.…”
Section: The Time Course Of Multiple Simple Featuressupporting
confidence: 88%
“…Going further than previous studies, we were able to show how multiple features of the same stimulus are coded simultaneously and sustained for prolonged periods. This prolonged coding of each feature support prior research showing feature coding in multiple areas of the visual pathway beyond V1 (e.g., Desimone et al, 1985;Groen et al, 2022;Kamitani and Tong, 2005;Marquardt et al, 2018;Seymour et al, 2009). We found distinct representations for each feature, reflecting separable neural populations and/or different codes of multiplexing cells specialised for coding each feature.…”
Section: The Time Course Of Multiple Simple Featuressupporting
confidence: 88%
“…Delayed normalization model paired with different filter shapes can account for both near-additive and sub-additive temporal summation. In VSDI, the measured normalization filter (in the denominator) was biphasic, whereas the normalization filter used to account for ECoG data, which were substantially sub-additive as fMRI BOLD signals, was monophasic [16, 32]. In Figure 3C and 3D, we demonstrated that with different normalization filter shapes, the model could account for both near-additive and sub-additive temporal summations.…”
Section: Resultsmentioning
confidence: 95%
“…The dataset was collected as part of a larger project funded by the NIH (R01MH111417). The methods for collecting and preprocessing the visual ECoG data have been described recently (Groen et al, 2022). For convenience, data collection methods below duplicate some of the text from the methods section of Groen et al, (2022) with occasional modifications to reflect slight differences in participants, electrode selection, and pre-processing.…”
Section: Methodsmentioning
confidence: 99%
“…To correct the delay, UMCU data were aligned to the NYU data based on a cross- correlation on the average event-related potentials (ERPs) across all stimulus conditions from the V1 and V2 electrodes from three participants (1 UMCU, 2 NYU). The delay in stimulus presentation was estimated to be 72ms, and stimulus onsets of the UMCU participants were shifted accordingly (Groen et al 2022). One NYU patient (Patient 3) had inaccurate trigger onset signals for each stimulus event due to a recording malfunction.…”
Section: Methodsmentioning
confidence: 99%